2006
DOI: 10.1063/1.2245194
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric effect of mildly conducting magnetostrictive/piezoelectric particulate composites

Abstract: A relatively simple model has been developed to study the magnetoelectric effect of magnetostrictive/piezoelectric dilute particulate composites. For illustrative purpose, we calculate the magnetoelectric voltage coefficients of particulate composites of NiFe 2 O 4 and lead zirconate titanate. By treating the inclusion/matrix as mildly conducting materials, we have reproduced all the key experimental features of magnetoelectric behavior of the particulate composites. In addition, the qualitative dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…As can be seen in figure 4c and as expected for well dispersed composites [30][31] no difference is noted in the ME response when composite thickness and AC applied field are changed. In this way, it can be concluded that the residual stress status of the composites, that strongly depends on film thickness and deeply affects the ME coupling, together with preferential nanoparticle orientation and interface defects [32], does not play a significant role in the processed composites.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As can be seen in figure 4c and as expected for well dispersed composites [30][31] no difference is noted in the ME response when composite thickness and AC applied field are changed. In this way, it can be concluded that the residual stress status of the composites, that strongly depends on film thickness and deeply affects the ME coupling, together with preferential nanoparticle orientation and interface defects [32], does not play a significant role in the processed composites.…”
Section: Resultssupporting
confidence: 76%
“…For higher concentrations, nanoparticles lead to the disruption of the ferroelectric copolymer phase [19], having as a result an abrupt decrease in the ME response of the nanocomposite. The theoretical fitting of this behavior was performed by using the model presented in [30][31]. In this model, the ME response α 33 can be expressed As expected and predicted by the theory, the good value of piezoelectric coefficient reached at 7wt% is not enough to obtain a good magnetoelectric coefficient in samples with low magnetostrictive nanoparticle concentrations since it is necessary a substantial presence of both ferroelectric and magnetostrictive phases [8,33].…”
Section: Resultsmentioning
confidence: 94%
“…Previously, we have proposed simple models for the effective piezoelectric properties of 0-3 composites and the longitudinal ME response for dilute particulate magnetostrictive-piezoelectric composites with spherical inclusions. 13,14 Fairly good agreement with experimental results has been obtained. To impart piezoelectric activity in a 0-3 ferroelectric composite, the material must first be subjected to a poling process for a sufficiently long duration to align the spontaneous polarization as well as to allow free charges to accumulate at the inclusion-matrix interfaces to counteract the depolarization field to stabilize the polariza-tion.…”
Section: Introductionsupporting
confidence: 75%
“…Another possible cause is the effect of electrical conductivities in the constituents, which allow charge accumulation at the inclusionmatrix interfaces, thus affecting the electric field in the piezoelectric matrix. 14 The previous article has suggested that the effective conductivity may increase rapidly with . Hence a tendency of decreasing ␣ with higher is observed.…”
Section: A Comparison With Experimental Datamentioning
confidence: 99%
“…Let λ x1 , λ y1 and λ z1 represent the induced strains in the magnetostrictive inclusions due to H 1 . According to the theory of elasticity, the stress T and strain e in the constituents in the x, y and z directions obey the following conditions [13,14]:…”
Section: Stresses and Strains In The Particulate Compositementioning
confidence: 99%